Tillering capacity and nitrogen fertilization in white oat - Follmann, Diego Nicolau; Silveira, Marcelo Santos; Pereira, Anderson Crestani; da Rosa, Guilherme Bergeijer; Cargnelutti Filho, Alberto; Lucio, Alessandro Dal’Col (Scientia Agraria Paranaensis, 2022)
Nitrogen fertilization enhances the tillering capacity of white oats and a greater number of fertile tillers is directly related to the increase in grains per area, which is related to grain yield. The objectives of this work were to evaluate the tillering capacity and the linear relationships between characters of white oat cultivars, associated with the use of nitrogen fertilization. The experiment was carried out in Santa Maria - RS, in a randomized block design, with the main plot comprising five white oat cultivars and the subplot comprising four doses of nitrogen applied as a top dressing when the crop had 3 developed leaves (0 kg ha-1, 50 kg ha-1, 100 kg ha-1, and 150 kg ha-1). Six hundred plants were sampled when the crop was at the full tillering stage and the characters were assessed: plant height (cm), height of first leaf insertion (cm), number of fully expanded leaves, number of tillers, stem diameter (cm), and dry matter phytomass (g). Nitrogen had a positive effect on the number of tillers, with the most effective doses being between 101.67 and 122.14 kg ha-1. The 122.14 kg ha-1 dose is recommended in order to achieve maximum technical efficiency for the production of tillers in the white oat crop, with emphasis on the URS Altiva cultivar, which had the highest number of tillers. The number of tillers and plant height have a positive linear relationship with dry matter phytomass and can be used for indirect selection.